(untitled) (Филологические заметки, 2019)
Analyzing contexts of the term “linguistic awareness” we can see different approaches to the phenomena of linguistic awareness. Some psycholinguists interpret this phenomena as products of mental activity, verbalized by lexical units. Meanwhile for lack of a lexical unit in a language it is possible to verbalize any content in a sentence. So psychologists discuss the psychophisiological basis of language competence and speech performance as a component of linguistic awareness. At least some linguists propose to distinguish linguistic awareness and communicative awareness. We try to precise the interpretation by determining connections of the phenomena with such kind of objects as mental activity, conscience, culture.